FOREIGN EXPERIENCES AND ANALYSIS OF COMPUTER MODELING TRAINING - Khurshid Alikulovich Markayev (American Journals, 2023)
This article is devoted to the problem of teaching computer modeling in foreign countries. The article suggests that this problem can be solved by offering specific elements and action programs from primary school age. The article is unique, and on foreign experience it will be possible to make sure that the issue of modeling is relevant and important.
Keywords: experience, modeling, national program, plan, technology, programs.